2016
DOI: 10.1080/0144929x.2016.1262900
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel longitudinal study of experiencing virtual presence in adolescence: the role of anxiety and openness to experience in the classroom

Abstract: Presence describes the feeling of reality and immersion that users of virtual/internet environments have. Importantly, it has been suggested that there are individual and contextual differences regarding susceptibility to presence. These aspects of presence have been linked to both beneficial and disadvantageous uses of the internet, such as online therapeutic applications and addictive internet behaviours. In the present study, presence was studied in relation to individual anxiety symptoms and classroomlevel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…There is a wide range of game genres, these can include racing, shooting, puzzle, fighting, simulation, and role-playing games, available both in single player and/or multiplayer formats ( Anderson et al, 2017 ; Hu, Stavropoulos, Anderson, Scerri, & Collard, 2018 ; Scerri, Anderson, Stavropoulos, & Hu, 2018 ). Recent studies have shown that IGD susceptibility appears to vary across these game genres, with MMO games consistently corresponding with a higher risk due to its unique structural characteristics ( Kuss & Griffiths, 2012 ; Stavropoulos, Kuss, et al, 2017 ; Stavropoulos, Wilson, Kuss, Griffiths, & Gentile, 2017 ; Stetina et al, 2011 ). In general, MMO games are typically made up of virtual worlds that embrace large numbers of gamers worldwide, while evolving in real time (i.e., independent of the ongoing participation of individual gamers) and in relation to the accomplishment of progressively higher and often collaborative goals and challenges ( Griffiths, Davies, & Chappell, 2004 ; Kuss & Griffiths, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a wide range of game genres, these can include racing, shooting, puzzle, fighting, simulation, and role-playing games, available both in single player and/or multiplayer formats ( Anderson et al, 2017 ; Hu, Stavropoulos, Anderson, Scerri, & Collard, 2018 ; Scerri, Anderson, Stavropoulos, & Hu, 2018 ). Recent studies have shown that IGD susceptibility appears to vary across these game genres, with MMO games consistently corresponding with a higher risk due to its unique structural characteristics ( Kuss & Griffiths, 2012 ; Stavropoulos, Kuss, et al, 2017 ; Stavropoulos, Wilson, Kuss, Griffiths, & Gentile, 2017 ; Stetina et al, 2011 ). In general, MMO games are typically made up of virtual worlds that embrace large numbers of gamers worldwide, while evolving in real time (i.e., independent of the ongoing participation of individual gamers) and in relation to the accomplishment of progressively higher and often collaborative goals and challenges ( Griffiths, Davies, & Chappell, 2004 ; Kuss & Griffiths, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significance of cultural factors for addictions ( Griffiths, 2005 ) and absorbing internet use in particular ( Stavropoulos, Wilson, et al, 2017 ), these have been under-explored in regards to IGD ( Pontes, 2018 ; Stavropoulos, Anderson, et al, 2018 ; Stavropoulos, Griffiths, et al, 2018 ). Specifically, cultural differences in relation to the presentation of addictions (i.e., prevalence, incidence, and clinical manifestations), as well as variations considering their associated risk factors have been suggested ( Landrine, Klonoff, & Brown-Collins, 1992 ; Stavropoulos, Anderson, et al, 2018 ; Wilsnack, Vogeltanz, Wilsnack, & Harris, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial presence theory has been widely used to understand technology-mediated communication such as virtual reality (Coxon et al 2016;Westerman et al 2015), video gaming (Murphy 2016;Williams 2014), and educational settings (Stavropoulos et al 2017). Bracken (2005) showed that watching high-definition television was associated with higher sense of spatial presence, and that higher sense of spatial presence is positively affected by higher emotional involvement with the consumed media (Wirth et al 2012).…”
Section: Problematic Instagram Use and Perceived Feeling Of Presencementioning
confidence: 99%
“…This experiment did not include a task type with various complicated VR settings, such as more applications based on string theory [23,27,28], as an example of a more difficult task that is beyond ordinary human spatial comprehension. In addition, a previous study indicated that the feelings of reality and immersion experienced by users familiar with VR environments might obscure comparisons of VR performance [2,25].…”
Section: Limitationsmentioning
confidence: 99%